Changing War : the British Army, the Hundred Days Campaign and The Birth of the Royal Air Force, 1918. - Sheffield, Gary.; Gray, Peter (London : Bloomsbury Publishing, 2013)
In 1918, the British Expeditionary Force (BEF) played a critical role in defeating the German army and thus winning the First World War. This 'Hundred Days' campaign (August to November 1918) was the greatest series of land victories in British military history. 1918 also saw the creation of the Royal Air Force, the world's first independent air service, from the Royal Flying Corps and the Royal Naval Air Service. Until recently, British histories of the First World War have tended to concentrate on the earlier battles of 1916 and 1917 and often underplayed this vitally important period. Chang.
9 The Genesis of Modern Warfare: The Contribution of Aviation Logistics10 The Genesis of Modern Air Power: The RAF in 1918; 11 The Battle of Amiens: Air-Ground Co-operation and its Implications for Imperial Policing; Introduction; The Battle of Amiens; The mechanics of air-ground co-operation; The implications for imperial policing; 12 The Battle of Amiens and the Development of British Air-Land Battle, 1918-45; Bibliography; Index.
Print version record.
eBooks on EBSCOhost
Keywords: Great Britain. -- Army. -- British Expeditionary Force; Great Britain. -- Royal Flying Corps -- History; Great Britain. -- Royal Naval Air Service -- History; Great Britain. -- Army. -- British Expeditionary Force; Great Britain. -- Royal Flying Corps; Great Britain. -- Royal Naval Air Service; World War, 1914-1918 -- Campaigns -- Western Front; World War, 1914-1918 -- Aerial operations, British; World War, 1914-1918 -- Naval operations, British; Guerre mondiale, 1914-1918 -- Campagnes et batailles -- Front occidental; HISTORY -- Europe -- Western; Military campaigns; Military operations, Aerial -- British; Western Front (World War (1914-1918)); Grossbritannien; 1914-1918; History